The Authority Relationship: Regional Head and His Deputy in the Regional Autonomy - Erga Yuhandra; Suwari Akhmaddhian; Anggit Anggiatna (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
The study aims to examine the Regional Head authority in the regional autonomy and to investigate the authority relationship between the Regional Head authority and his Deputy from legal and political perspectives. This study employed a doctrinal research method involving legal material sources (the laws and regulations), court decisions/judgments, legal theories, and scholars' perspectives. The findings revealed the Regional Head authority is clearly stated in Article 65 of Law Number 9 of 2015 concerning Regional Government, such as to lead the implementation of government affairs–the regional authority based on the laws and policies established with the DPRD, to maintain public peace and orderliness, and to compile and to submit regional regulations draft. Normatively,  the Regional Head and his Deputy have their respective duties, the authority relationship. In this case, the Deputy Regional Head assists the Regional Head in the governance to acquire the fullest services for the community. In short, in terms of authority, the Regional Head is an extension of the President-- the full holder of goverment power. In terms of the authority relationship, different opinions between the Regional Head and his Deputy are frequently occurred as in the political views